Urbanisation, plant traits and the composition of urban floras - Williams, Nicholas S.G.; Hahs, Amy K.; Vesk, Peter A. (Perspectives in plant ecology, evolution and systematics, 2015)
Given the increasing prevalence of cities, a better mechanistic and functional understanding of plant responses to urbanisation will assist biodiversity conservation and the provision of ecosystem services. Plant functional traits offer an opportunity to do this. To explore the relationship between plant traits and the urban environment, we synthesised the results of 29 studies that specifically examined plant traits or niche indicators (e.g. Ellenberg numbers) of urban floras. Niche indicators for nutrients, temperature and alkalinity were found to consistently increase across many studies. Some plant traits (e.g. woodiness, seed mass and height) tended to increase in response to urbanisation, while other traits have mixed responses and many other traits are understudied. We propose that variability in the observed responses is linked to the consistency and strength of urban stressors acting on those traits, and the importance of local factors. Our synthesis highlights the complexity of urban plant–environment interactions with many traits influenced by multiple abiotic, biotic and disturbance effects of urbanisation. Multiple stressors make it difficult to detect trends in urban plant trait signatures unless one urban stressor drives a particularly strong response or multiple stressors act on the response in the same direction. While our review has developed a better understanding of how urbanisation may assemble urban floras, further advances can be gained through studies that focus on specific urbanisation processes, measurable morphological traits and data curation and analyses that facilitate meta-analysis.